Nanomechanical Characterization of the Deformation Response of Orthotropic Ti–6al–4v - Garcia-Herrera, C (John Wiley and Sons Inc, 2021)
The nanoindentation-induced mechanical deformation response is applied to identify the orthotropic elastic moduli using the Delafargue and Ulm method as well as to validate the asymmetric orthotropic CPB06 nonlinear plasticity model required in simulations of nonuniform macroscopic mechanical response of the Ti–6Al–4V alloy. Scanning electron microscope (SEM) technique allows to select the maximum penetration depth for the indentation in the deformed alpha phase and alpha–beta interphase, α and α/β, respectively. The apparent macromechanical response can be successfully derived from several residual imprints conducted at micro- and/or submicrometric length scale and distributed throughout samples of the investigated bulk alloy, as demonstrated by correlation with finite element simulations based on the orthotropic elastoplastic model. The accurate numerical response obtained validates the material model and the Delafargue and Ulm approach, opening a window for next generation identification methods of macromechanical plasticity models with hybrid experimental–numerical method based on instrumented indentation and the use of SEM technique. © 2021 Wiley-VCH GmbH